Prevention in mental health : lifespan perspective - Jeste, Dilip V. ;Bell. Carl C. (Philadelphia, Pennsylvania : Saunders an imprint of Elsevier, Inc., 2011)
Behavorial vaccines and evidence-based kernels: nonpharmaceutical approaches for the prevention of mental, emotional, and behavioral disorders -- Prevention of adolescent depression -- Preventing postpartum depression -- Youth homicide prevention -- Human immunodeficiency virus prevention with youth -- Psychological protective factors across the lifespan : implications for psychiatry -- Prevention in psychiatry : effects of healthy lifestyle on cognition.
Behavioral vaccines and evidence-based kernels : nonpharmaceutical approaches for the prevention of mental, emotional, and behavioral disorders / Dennis D. Embry -- The prevention of adolescent depression / Tracy R.G. Gladstone, William R. Beardslee, and Erin E. O'Connor -- Preventing postpartum depression / Laura J. Miller and Elizabeth M. LaRusso -- Preventing depression in later life : state of the art and science circa 2011 / Fawzi Hindi [and others] -- Prevention of posttraumatic stress disorder / Heather M. Sones, Steven R. Thorp, and Murray Raskind -- Prevention of the first episode of psychosis / William R. McFarlane -- Prevention of metabolic syndrome in serious mental illness / Rohan Ganguli and Martin Strassnig -- Prevention of dementia / Rodolfo Savica and Ronald C. Petersen -- Genomics for disease treatment and prevention / Cinnamon S. Bloss, Dilip V. Jeste, and Nicholas J. Schork -- Internet-based depression prevention over the life course : a call for behavioral vaccines / Benjamin W. Van Voorhees [and others] -- Infusing protective factors for children in foster care / Gene Griffin [and others] -- Youth homicide prevention / Kobie Douglas and Carl C. Bell -- Human immunodeficiency virus prevention with youth / Dominica F. McBride and Carl C. Bell -- Psychological protective factors across the lifespan: implications for psychiatry / Ipsit V. Vahia [and others] -- Prevention in psychiatry : effects of healthy lifestyle on cognition / David A. Merrill and Gary W. Small.
Includes bibliographical references and index.
Keywords: MENTAL ILLNESS -- PREVENTION